Newness in Old Testament prophecy : an intertextual study - Leene, Henk. (Leiden : BRILL, 2014)
In Newness in Old Testament Prophecy: An Intertextual Study Henk Leene examines literary and text-genetic relations between the promises regarding new things in Isaiah, Jeremiah and Ezekiel, paying due attention to the new song heralding Yhwh's kingship in the Psalms.
Introduction -- What is new in prophecy -- Intertextuality -- 'Newness' in the Psalms on Yhwh's kingship, Deutero- and Trito-Isaiah -- Perspective -- Psalms on Yhwh's kingship -- A new song : Psalms 96 and 98 -- Psalm 96 -- Psalm 98 -- Contextual embedding of Psalms 96 and 98 -- Complementary natures -- Diachronic aspects -- Enthronement according to Psalms 93-100 -- Enthronement and eschatology -- Deutero-Isaiah -- New and hidden things : Isaiah 40-55 -- Methodology -- Isaiah 41:14-16 -- Isaiah 42:5-9 -- Isaiah 42:10-13 -- Isaiah 43:16-21 -- Isaiah 48:1-11 -- A synchronic approach -- Dramatic Progression in Isaiah 40-55 -- First-last-coming-new in Isaiah 41-48 -- A diachronic approach -- Redaction-critical theories on Isaiah 40-55 -- First-new : relations with Isaiah 1-39 -- Relations with Psalms 96 and 98 -- In search of the hidden structure : Deutero-Isaiah in dialogue with Psalms 93-100 on Yhwh's kingship -- The servant as present time eschatology -- Trito-Isaiah -- A new heaven and a new earth : Isaiah 65 -- Structure of Isaiah 65 -- Isaiah 65 set in its context -- Diachronic questions -- Redaction-critical deliberations -- Relative and absolute dating of Deutero- and Trito-Isaiah -- Relations with Isaiah 40-55 -- The dawn of apocalyptic? -- 'Newness' in Ezekiel -- 3.0 perspective -- Ezekiel -- A new heart and a new spirit : Ezekiel 18 and 36 -- Ezekiel 18:21-32 -- Ezekiel 36:16-38 -- The embedding of Ezekiel 18 and 36 in the book -- Diachronic questions -- Papyrus 967 -- Stratification of Ezekiel 36:16-38? -- Ezekiel's newness passages in diachronic perspective -- A comparison between Ezekiel 36 and Psalm 51 -- Jeremiah -- A new creation and a new covenant : Jeremiah 30-31 -- Jeremiah 31:21-22, 23-26 -- Jeremiah 31:27-30, 31-34 -- Literary structure of Jeremiah 30-31 -- The embedding of Jeremiah 30-31 : a few aspects -- Diachronic questions -- Redaction-critical theories on Jeremiah 30-31 -- Jeremiah's promises in diachronic perspective -- Diachronic relations between Jeremiah and Ezekiel -- Golah-orientated redaction? -- 'New' at the crossroads of two prophetic traditions -- Retrospect and perspective -- Relations between Ezekiel and Isaiah 40-55 -- Relations between Isaiah and Jeremiah 30-31 -- Linguistic, generic and compositional agreements -- Diachronic approach -- The promise of the new in Isaiah and Jeremiah -- The new as scenario and programme : conclusion -- chronology -- Intertextual dialogue -- Yhwh-Kingship Psalms, Deutero- and Trito-Isaiah -- Ezekiel and Jeremiah -- Ezekiel and Isaiah, Isaiah and Jeremiah -- Eschatology -- Selected bibliography -- Index of authors -- Index of biblical texts.
Includes bibliographical references (pages 359-372) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Bible. -- Prophecies; Bible. -- Criticism, interpretation, etc; Bible; Bibel; Bibel; RELIGION -- Biblical Studies -- Old Testament; RELIGION -- Judaism -- Sacred Writings; Das Neue; Exegese; Prophetie; Prophecies; Criticism, interpretation, etc